DEVELOPMENT OF PROJECT-BASED LOGO AND TYPOGRAPHY LEARNING MODEL: AUTO-ETHNOGRAPHY STUDY AND CLASS ACTION RESEARCH TO IMPROVE STUDENTS' MOTIVATION AND UNDERSTANDING AT SMP NEGERI 3 GUNTUR DEMAK - Wijaya, Shella Henry; Jazuli, Muhammad; Wibawanto, Wandah (Imajinasi: Jurnal Seni, 2025)
This study aims to develop an effective project-based logo and typography learning model in improving the motivation and understanding of grade VII students at SMP Negeri 3 Guntur, Demak. This study employs a qualitative approach, combining autoethnography and classroom action research (CAR). Autoethnography is used to reflect on the researcher's experience as a teacher, while CAR is used to test and refine the learning model through two cycles of action. Data were collected through observation, teacher reflective journals, learning motivation questionnaires, student work, interviews, and visual documentation. The project-based learning model is designed to enable students to develop visual skills through creative, collaborative, and applicative processes. The results of the study indicate that this model can enhance students' intrinsic motivation, particularly in terms of autonomy, competence, and social connectedness, in line with Self-Determination Theory (Ryan & Deci, 2000). In addition, students' understanding of visual design concepts also increased, as indicated by the quality of the logo and typography projects assessed using an assessment rubric. The researcher's reflection shows that this approach is effective in creating contextual, meaningful, and challenging learning. This study suggests the wider application of this model in schools with similar conditions to strengthen visual skills-based learning.